Intergenerational Altruism, Dynastic Equilibria and Social Welfare - Bernheim, B. D. (Review of Economic Studies, 1989)
The purpose of this paper is to explore the welfare properties of dynastic equilibria. There are three central findings. First, under relatively weak conditions, welfare optima cannot be implemented as dynastic equilibria with positive levels of transfers. Second, intergenerational altruism ordinarily renders the objectives of social planners dynamically inconsistent, thereby making implementation of welfare optima problematic. Third, if a planner successfully resolves dynamic inconsistency by committing himself to respect the preferences of deceased generations, then, in a specific set of cases, dynastic equilibria are approximately welfare optimal. Copyright 1989 by The Review of Economic Studies Limited.